Work-Life Balance and Organizational Commitment of Hospitals in Delta State - Elvis Odile Okokpele; Ekpeni Ogechukwu Perpetual; Okwise Young U; Olannye A. Peter (Journal of Behavioral Economics, Finance, and Management Insights, 2025)
The research aimed to evaluate how maintaining a healthy balance between work and personal life influences the loyalty of staff in hospitals located in Delta State. To achieve this, a survey research method was utilized, involving 213 workers from five private medical facilities in Asaba, Delta State. Hence, the research was conducted with a group of 139 workers, determined using the Yamen formula for sample size estimation. The participants were chosen using the method of stratified random sampling. Data was gathered using a structured questionnaire, and reliability was confirmed through a test-retest method. Data analysis involved the use of both descriptive and inferential statistical methods. Results indicated that flexible work schedules, leave policies, remote work options, and efficient time management all positively influenced employee commitment to their organizations. The study's overall conclusion was that work-life balance plays a significant role in fostering strong organizational dedication among hospital staff in Delta State. It was suggested that HR managers invest in technology and infrastructure to support remote work, as well as allocate resources for employees' access to necessary tools and secure remote system connections in healthcare settings.